ANALISIS PEMBELAJARAN DENGAN CASE METHOD PADA MATERI DINAMIKA LITOSFER DAN DAMPAKNYA TERHADAP KEHIDUPAN DALAM PEMBELAJARAN GEOGRAFI DI MAN LIMA PULUH KOTA - Syahrandi, Andika; Nofrion, Nofrion (DEPARTEMEN GEOGRAFI FIS UNP, 2024)
ABSTRACT This study aims to discuss the application of Case Mathod to the dynamics of the lithosphere and its impact on life to improve student learning outcomes in MAN Lima Puluh Kota geography. This research is an experimental research (Quasi Experiment Design) with pretest posttest control group design. Using a quantitative approach. Sampling using purposive sampling. The sample in this study was class X IPS as the experimental class, totaling 19 people and class X IPK as the control class, totaling 18 people. The research instruments were in the form of learning achievement tests and study participation observation sheets. The results showed that the average pretest score for the experimental class was 45.90 and that for the control class was 48.14. Then the posttest value of the experimental class was 76.31 and that of the control class was 56.48. So that the N-Gain score for the experimental class was 0.56 which was in the medium criteria and for the control class the N-Gain score was 0.16 which was in the low criteria. So this shows that the N-Gain score of the experimental class is greater than the control class. The results of the hypothesis test with the t test show that the value of Tcount is 10.43 and Ttable is 1.68 which indicates the value of Tcount > Ttable, then Hɑ is accepted meaning that the application of the Case Method in geography learning can improve learning outcome to the dynamics of the lithosphere and its impact on life. Keywords: Learning Outcomes, Case Method, Lithosphere Dynamics and their Impact on Life